Qatar‘s Islamweb fatwa on the limits of relationship between Muslims and non-Muslims: an analysis - Muhammad, Saud; Abdul Rahim, Adibah (IIUM Press, 2020)
The relationship between Muslims and non-Muslims is one of the central point of discussions in the fiqhi discourses of Islamic tradition. The Muslim jurists throughout Islamic history defined the extent of relationship between Muslims and non-Muslims is based on the doctrine of al-walā‟ wa al-barā‟ as stated in the revealed discourses. This paper analyzes one of the scopes of relationship, that is, friendship. Some scholars including Islamweb muftis argued that the mode of friendship is connecting with loyalty (alwalā‟), and based on such understanding, they claimed that friendship with non-Muslims is not permissible. After analyzing the views of the Islamweb muftis on friendship, the paper found that their definition of friendship is not in line with modern understanding of friendship. In the modern world order context, friendship carries various interpretations. Therefore, this paper did not agree with the fatwā issued by Islamweb muftis which prohibits friendship with non-Muslims. The paper argued that friendship with non-Muslims is conditional, essential (sometimes if not always) and strategic in the current world to serve the greater purpose.